2013
DOI: 10.1016/j.amjcard.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Kinase Adenosine Triphosphate and Phosphocreatine Energy Supply in a Single Kindred of Patients With Hypertrophic Cardiomyopathy

Abstract: A lethal and extensively characterized familial form of hypertrophic cardiomyopathy (HC) is due to a point mutation (Arg403Gln) in the cardiac β-myosin heavy-chain (MHC) gene. Although this is associated with abnormal energy metabolism and progression to heart failure in an animal model, in vivo cardiac energetic shave not been characterized in patients with this mutation. Noninvasive phosphorus saturation transfer magnetic resonance spectroscopy was used to measure the adenosine triphosphate (ATP)supplied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 30 publications
5
36
1
Order By: Relevance
“…Taken together with the findings in the ZDF rat, our data suggest that a decrease in CK activity is not a major driver of cardiac energetic deficiency in the cardiomyopathy of MHD, but rather, support the thesis proposed by Bashir et al [34] that the increase in the CK rate constant is a compensatory response that helps to maintain a normal flux through CK in the face of a decrease in [PCr] [34]. Interestingly, in other models of HFpEF such as pressure overload [48] and hypertrophic cardiomyopathy [47] CK flux is decreased, suggesting that the energetic profile in “HFpEF” may be heterogeneous and related to the underlying etiology.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Taken together with the findings in the ZDF rat, our data suggest that a decrease in CK activity is not a major driver of cardiac energetic deficiency in the cardiomyopathy of MHD, but rather, support the thesis proposed by Bashir et al [34] that the increase in the CK rate constant is a compensatory response that helps to maintain a normal flux through CK in the face of a decrease in [PCr] [34]. Interestingly, in other models of HFpEF such as pressure overload [48] and hypertrophic cardiomyopathy [47] CK flux is decreased, suggesting that the energetic profile in “HFpEF” may be heterogeneous and related to the underlying etiology.…”
Section: Discussionsupporting
confidence: 57%
“…While decreased CK activity has been observed in systolic heart failure [31,32] and hypertrophic cardiomyopathy [47], relatively little is known about CK function in MHD. Of note, our findings are consistent with those of Bashir et al [34], who likewise found that the forward CK reaction rate constant was higher and CK flux was preserved in hearts from diabetic Zucker Diabetic Fatty (ZDF) rats.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that myocardial phosphocreatine was significantly decreased by 24% in HCM patients with a β-myosin heavy chain mutation compared with controls; pseudo-first-order creatine kinase rate constant was 26% lower and the forward creatine kinase flux 44% lower in HCM. 3 However, in this study, myocardial strain did not correlate with the metabolic indexes. Investigations of cardiac energetics have generally used magnetic resonance spectroscopy.…”
Section: See Article By Güçlü Et Alcontrasting
confidence: 74%
“…The FAST method has been deployed in a number of studies (Table ) in patients with heart disease ; knormalfCK values have been shown to be a more sensitive indicator of heart failure than the PCr/ATP ratio . Furthermore, CK flux values have been shown to be even more sensitive than knormalfCK values . The BOAST method will open up the possibility of measurements of regional myocardial knormalfCK values, making the technique more relevant to regional myocardial disease.…”
Section: Discussionmentioning
confidence: 99%